Studi Perbandingan Antara Jump Shoot dengan Shooting ditempat Menggunakan Dua Tangan diatas Kepala dalam Permainan Bola Basket Pada Siswa Putra SMA Tarvid Ende - Mbabho, Finsensius (LPPM Institut Pendidikan Nusantara Global, 2024)
This research is entitled Comparative Study between Jump Shoot and Shooting in Place Using Two Hands Above the Head in Basketball Games among Male Students at Tarvid Ende High School in 2023. The method used is Expost Facto research, Expost facto is a research method where manipulation (treatment) of the independent variable has been carried out. happened previously so that the research does not need to provide further treatment, just the effect on the dependent variable. The researcher can draw the following conclusion: